PENGARUH GAYA KEPEMIMPINAN DAN KEMAMPUAN SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU SMA NEGERI 2 PROBOLINGGO - jurnalpps pps; Hakam Basori (Jurnal Manajerial Bisnis, 2021)
Schools as educational institutions need principals who are able to lead and manage schools professionally. The purpose of this research is to describe the principal's leadership style, principal's supervision ability and teacher performance of Probolinggo High School 2 2019 and to know the significant influence of the principal's leadership style, principal's supervision ability, partially or simultaneously on teacher performance. The population in this study were all teachers of Probolinggo 2 Public High Schools, totaling 44 people. Sampling using census sampling method. The results of the descriptive analysis show that the chief leadership style the mean school of 3,950, the principal supervision ability of the mean 3,740 and the teacher's performance with a mean of 3,580 are already in very good condition (interval). Principal leadership style, principal supervision ability, partially or simultaneously significant effect on teacher performance.